THE ROLE OF ESG DISCLOSURE QUALITY IN SHAPING INVESTOR RISK PERCEPTION IN POST-PANDEMIC CAPITAL MARKETS - Rita J D Atarwaman; Amiruddin Amiruddin; Dharmawati Dharmawati (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
Significant changes in the capital market landscape following the COVID-19 pandemic have heightened investor attention to non-financial factors, particularly the quality of Environmental, Social, and Governance (ESG) disclosures. Global economic uncertainty, increasing systemic risk, and demands for greater transparency are encouraging investors to evaluate investment risk not only based on financial performance but also through sustainability information provided by companies. This study aims to examine the role of ESG disclosure quality in shaping investor risk perceptions in the post-pandemic capital market. The method used is a systematic literature review of scientific articles, institutional reports, and relevant academic publications that discuss the relationship between ESG disclosure, risk perception, and investment decision-making. The study results indicate that high-quality ESG disclosure contributes to lower investor risk perceptions by increasing transparency, reducing information asymmetry, and strengthening trust in corporate resilience and governance. Furthermore, credible and consistent ESG disclosures have been shown to be a positive signal for investors in assessing a company's ability to face long-term risks, particularly in the context of post-pandemic uncertainty. These findings underscore the importance of ESG as a strategic element in corporate communication to the market and the implications for regulators and capital market players in promoting quality sustainability reporting practices.